Automatic Dryer for Shoe using Incandescent Bulbs - Mat Akir, Rohaida; Shukor, Mohd Syafiq (Evolution in Electrical and Electronic Engineering, 2021)
Nowadays, climate change makes weather unpredictable and sometimes on a rainy day, they need to dry their shoe in a very short time. The automatic dryer is intended to enhance human life to change the traditional technique to the modern method of drying. The primary goal of this research is to create a prototype for drying without depends on sunlight. Besides, the automatic dryer can be more convenient for people who are too busy and have limited space in the house to drying shoes. The system automatically operated and used Arduino Uno to act as the microcontroller. The automatic dryer consists of a sensor for temperature and humidity. The temperature and humidity condition is controlled by bulbs, fans and buzzer to ensure the shoe is dry in good condition. The sensor is played a role to conduct the system of the automatic dryer. It is responsible for running the program and controls all the modules needed for the system to work. The predicted outcome of this research is that we can automatically help the peoples drying the shoe anytime within a short time.